Edible fungal polysaccharides, the gut microbiota, and host health. (1st December 2021) - Liang, Jingjing; Zhang, Meina; Wang, Xingnan; Ren, Yichen; Yue, Tianli; Wang, Zhouli; Gao, Zhenpeng
Abstract: The plasticity of the gut microbiota (GM) creates an opportunity to reshape the biological output of gut microbes by manipulating external factors. It is well known that edible fungal polysaccharides (EFPs) can reach the distal intestine and be assimilated to reshape the GM. The GM has unique devices that utilize various EFPs and produce oligosaccharides, which can selectively promote the growth of beneficial bacteria and are fermented into short-chain fatty acids that interact closely with intestinal cells. Here we review EFPs-based interventions for the GM, particularly the key microorganisms, functions, and metabolites. In addition, we discuss the bi-directional causality between GM imbalance and diseases, and the beneficial effects of EFPs on host health via GM. This review can offer a valuable reference for the design of edible fungal polysaccharide- or oligosaccharide-based nutrition interventions or drug development for maintaining human health by targeted regulation of the GM. Highlights: EFPs could regulate the gut microbiota (GM). The GM degrades polysaccharides through the synergism of CAZymes. Imbalance of the GM is causative to host health. Some consistent changes of the GM have been observed for specific diseases. EFPs intervention is an effective mean of disease prevention.